Supervision of the National Standardization Agency (BSN) Related to the Rising Circulation of Helmet that Does not Accept the Indonesian National Standard (SNI) Case Study in Medan City - Sinaga, Irfan Fandika; Ramadani, Ramadani (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
This research is motivated by the widespread distribution of non-SNI helmets in the city of Medan. Even though a helmet is a driving safety tool it is mandatory to use and pay attention to its quality. The aim and objective are to find out how far the role of BSN is in supervising the circulation of non-SNI helmets and what factors have caused the widespread circulation of non-SNI helmets in the Medan city market. The research method used in this research is qualitative research with an empirical legal approach based on a statutory approach - law and case approach. The data collection carried out in this research was a literature study where researchers used library research as a method of collecting data and information and also used semi-structured interviews so that researchers got specific answers related to problems. The results of the study are that there are still several helmet shops in Medan that sell cheap helmets and do not comply with the Indonesian National Standard due to the lack of knowledge about the regulations for selling SNI helmets. Then the lack of supervision and outreach by BSN and related agencies. The conclusion is that regulations regarding supervision are listed in Article 58 of Law Number 20 of 2014 concerning Standardization and Conformity Assessment. However, the implementation is still lacking. Helmets that do not meet SNI are still being traded in several shops in the city of Medan. Supervision and socialization from BSN or from the Service to helmet shops in Medan City is still minimal. The researchers’ hope for the National Standardization Agency (BSN) and related agencies is to tighten supervision of cheap helmets that do not comply with the Indonesian National Standard (SNI) and also to actively disseminate information to shops and the public. Thus, the rules can be enforced and not detrimental to any party.